Age-specific reference values for low psoas muscle index at the L3 vertebra level in healthy populations: A multicenter study - Kong, Ming; Lin, Ning; Wang, Lili; Geng, Nan; Xu, Manman; Li, Shanshan; Song, Wenyan; Zhou, Ying; Piao, Yuetong; Han, Zuoqing; Guo, Rong; Yang, Chao; et al. (Frontiers in Nutrition, 2022)
Background & Aims The progressive and generalized loss of skeletal muscle mass, strength and physical function is defined as sarcopenia. Sarcopenia is closely related to the prognosis of patients. Accurate diagnosis and adequate management of sarcopenia are crucial. The psoas muscle mass index taken at the third lumbar vertebra (L3-PMI, cm2/m2) is one of the established methods for evaluating skeletal muscle mass. However, the cutoff values of L3-PMI for diagnosis of sarcopenia are not yet to be clarified in Asian populations. We attempted to establish reference values for low L3-PMI that would be suitable for defining sarcopenia in the Northern Chinese population. Methods This was a retrospective, multicenter cross-sectional study. A search of abdominal CT imaging reports was conducted in four representative cities in northern China. Transverse CT images were measured using the analysis software Slice-O-Matic. Low psoas muscle index was defined as the 5th percentile or mean-2SD of the study group. Results 1787 healthy individuals in the study were grouped by age. The sex and number of people in each group were similar. L3-PMI had a negative linear correlation with age, and a strong correlation with the skeletal muscle index taken at the third lumbar vertebrae (L3-SMI, cm2/m2). The L3-PMI reference values in males were 5.41 cm2/m2 for 20–29 years, 4.71 cm2/m2 for 30–39 years, 4.65 cm2/m2 for 40–49 years, 4.10 cm2/m2 for 50–59 years and 3.68 cm2/m2 for over 60 years by using 5th percentile threshold. Similarly, the reference values in females were 3.32 cm2/m2, 3.40 cm2/m2, 3.18 cm2/m2, 2.91 cm2/m2 and 2.62 cm2/m2. When using mean-2SD as the reference, the values for each age group were 4.57 cm2/m2, 4.16 cm2/m2, 4.03 cm2/m2, 3.37 cm2/m2, 2.87 cm2/m2 for males and 2.79 cm2/m2, 2.70 cm2/m2, 2.50 cm2/m2, 2.30 cm2/m2, 2.26 cm2/m2 for females, respectively. Conclusions We defined the reference values of age-specific low skeletal muscle mass when simply evaluated by L3-PMI. Further study about the association of sarcopenia using these reference values with certain clinical outcomes or diseases is needed.